2019
DOI: 10.1186/s12936-019-2703-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing local-scale heterogeneity of malaria risk: a case study in Bunkpurugu-Yunyoo district in northern Ghana

Abstract: BackgroundBayesian methods have been used to generate country-level and global maps of malaria prevalence. With increasing availability of detailed malaria surveillance data, these methodologies can also be used to identify fine-scale heterogeneity of malaria parasitaemia for operational prevention and control of malaria.MethodsIn this article, a Bayesian geostatistical model was applied to six malaria parasitaemia surveys conducted during rainy and dry seasons between November 2010 and 2013 to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…Another limitation is the fact that the time of day spent in each locality was not accounted for, which can affect the probability for malaria infection, due to vector activity preferences. Seasonality attributed to malaria transmission dynamics may display an important influence in this study, as reported in the literature [3,31,32,34,37].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Another limitation is the fact that the time of day spent in each locality was not accounted for, which can affect the probability for malaria infection, due to vector activity preferences. Seasonality attributed to malaria transmission dynamics may display an important influence in this study, as reported in the literature [3,31,32,34,37].…”
Section: Discussionsupporting
confidence: 62%
“…Differences in malaria prevalence along rural-urban gradients can be explained by ecological, social, and behavioural factors [7][8][9]31]. In general, urban areas present certain conditions, such as housing, drainage network, pavement and easier access to health care, that contribute to decreased malaria prevalence compared to rural areas [32]. According to Braz et al [33], a spatial dependency is noted for malaria in the Amazon Basin, with differing characteristics between municipalities, states and international borders, reinforcing the importance of monitoring malaria clusters and integrative control actions.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-scale estimates of malaria spatio-temporal variations using methods presented here can then be used to characterize local socio-economic and environmental drivers of malaria risk, paving the way to the development of early warning or forecasting systems that could further guide local malaria control. Malaria heterogeneity and its drivers are commonly modelled at the national and regional level [ 62 64 ], but malaria can have extensive spatial variability in relatively small areas [ 42 , 43 , 65 ]. After adjustment, we observed significant spatial variations in malaria incidence in communities across the district, with 7% the population living in areas where annual incidence was twice the district’s average, as well as multiple short-term, localized hotspots during the study period (Additional file 3 : Video S1).…”
Section: Discussionmentioning
confidence: 99%
“… 101 Several studies on applying environmental variables that influence the transmission of malaria had applied and reported best-fit models with distance to streams, distance to main road, distance to health facility, and distance to border. 32 , 102 104 The experts in this study identified two proxy indicators of access to treatment and care, distance to road and distance to health facilities. Distance of a place from roads could affect or determine the effectiveness of measures to be taken to control the risk of malaria infestation.…”
Section: Discussionmentioning
confidence: 99%